Bipolarity between agile Performance of Public Contracts and the Coercive Measures of the administration - Palacio Jaramillo, Maria Teresa (2020)
The following article aims to raise awareness regarding relevant issues about the way in which the Public administration has been practicing its sanctionatory attributes in regards to the public procurement contracts performance.This analysis strives to display how some excesses are being committed in the execution of this power, having a negative effect in public procurement by not achieving the goal of fighting effectively against immoral conducts and corruption. The purpose of this paper is to expose the misconception entailing the execution of attributes of the executive branch, as well as, the incautious legal measures that have had negative results in this sector.